2011
DOI: 10.1007/s00122-011-1654-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions involved in the inhibition of heading by heading date QTL, Hd2 in rice under long-day conditions

Abstract: Heading date is the one of the most important traits in rice breeding, because it defines where rice can be cultivated and influences the expression of various agronomic traits. To examine the inhibition of heading by Heading date 2 (Hd2), previously detected on the distal end of chromosome 7's long arm by quantitative trait locus (QTL) analysis, we developed backcross inbred lines (BILs) from Koshihikari, a leading Japanese cultivar, and Hayamasari, an extremely early heading cultivar. The BILs were cultivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…SD expression of VRN2 was also reported in the day-neutral Ppd-D1a wheat mutant, which carries a deletion in the promoter of Ppd-D1a associated with constitutive expression of the gene (Turner et al, 2013). Similarly, in rice, Ghd7 and OsPRR37, homologous to VRN2 and PPD1, exhibited epistatic interactions in the control of flowering time of rice populations grown in the field under different photoperiods (Fujino and Sekiguchi, 2005;Shibaya et al, 2011). These studies in rice and wheat suggested that PPD1/OsPRR37 and VRN2/Ghd7 might interact; however, the mechanism that controls the activation of VRN2 expression in response to photoperiod remains unclear.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…SD expression of VRN2 was also reported in the day-neutral Ppd-D1a wheat mutant, which carries a deletion in the promoter of Ppd-D1a associated with constitutive expression of the gene (Turner et al, 2013). Similarly, in rice, Ghd7 and OsPRR37, homologous to VRN2 and PPD1, exhibited epistatic interactions in the control of flowering time of rice populations grown in the field under different photoperiods (Fujino and Sekiguchi, 2005;Shibaya et al, 2011). These studies in rice and wheat suggested that PPD1/OsPRR37 and VRN2/Ghd7 might interact; however, the mechanism that controls the activation of VRN2 expression in response to photoperiod remains unclear.…”
mentioning
confidence: 66%
“…However, Saito et al (2012) showed that OsElf3 controlled the expression of both Hd1 and Ghd7 and suggested that both genes may interact to control Hd3a. In addition, Shibaya et al (2011) demonstrated that Ghd7 interacted with Hd2, which was identified as OsPRR37, the rice homolog of Ppd-H1. Interestingly, our expression analysis revealed that the functional allele of Ppd-H1 was associated with higher expression levels of VRN-H2 under LDs in the nontransgenic F2 genotypes with a winter allele at VRN-H2.…”
Section: Overexpression Of Hvco2 and Hvco1 Induced The Expression Of mentioning
confidence: 99%
“…Interactions between Hd2 and other flowering genes were firstly reported by Yamamoto et al (2000) and Lin et al (2000), showing that this gene was interacted with Hd1 , Hd3 and Hd6 but the interaction changed under different day-length conditions. Later, Hd2 was also found to interact with other genes such as Ghd7 and Ghd8 (Fujino and Sekiguchi, 2005; Gu and Foley, 2007; Shibaya et al, 2011; Kim et al, 2013). Consequently, the response of Hd2 to photoperiod varies depending on genetic backgrounds and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…First, only RM248 located in the Hd2 region was used for selecting NILs used by Yan et al (2013) and genotype information on other heading date genes were not clarified, it is possible that functional alleles at Ghd7 or other loci that required for the PS activity of Hd2 were preserved in the genetic background of the NILs they used. Second, Hd2 has been found to interact with multiple genes (Lin et al, 2000; Yamamoto et al, 2000; Fujino and Sekiguchi, 2005; Gu and Foley, 2007; Shibaya et al, 2011; Kim et al, 2013), thus, its effects under LDs and SDs are highly diversified.…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress in rice functional genomics is being made since the completion of the international rice genome sequencing project (Chen et al, 2011) which offers tremendous opportunities for breeders to improve this important crop by molecular breeding. Many molecular and genetic analyses have been performed on rice different traits such as: heading date (Izawa et al, 2003;Izawa, 2007;Shibaya et al, 2011), spikelet sterility (Ikehashi and Araki, 1986;Sawamura and Sano, 1996;Zhang and Lu, 1996;Wan et al, 1998;Wang et al, 1998;Yan et al, 2000;Ji et al, 2005;Zhao et al, 2006;Zhang et al, 2011), leaf size Shen et al, 2003;Kobayashi et al, 2006;Yue et al, 2006;Tong et al, 2007;Farooq et al, 2010) and yield components traits Erik et al, 2002;Ishimaru, 2003;Thomson et al, 2003;Yoon et al, 2006).…”
Section:  Non-conventional Approachesmentioning
confidence: 99%